Analysis of unmanned aerial vehicle airframe materials on circularly polarized antenna radiation characteristics - Wahyudi, Wahyudi; Setyadewi, Imas Tri; Sakti, Mohammad Amanta Kumala; Prabowo, Yanuar; Hadiyanti, Donatina Miswati; Rahayu, Novelita; Muzayadah, Nurul Lailatul; Wahyudi, Agus Hendra; Guno, Yomi; Praludi, Teguh; Santosa, Cahya Edi; Sumantyo, Josaphat Tetuko Sri (Institute of Advanced Engineering and Science, 2025)
This paper presents an experimental examination of how unmanned aerial vehicle (UAV) airframe materials affect the electromagnetic characteristics of the airborne circularly polarized (CP) payload antenna. This study specifically investigates the received signal from the circularly polarized synthetic aperture radar (CP-SAR) antenna installed within the fuselage of the lapan surveillance UAV (LSU). In the airborne CP-SAR experiment, broadband CP microstrip subarray antennas were used along with LSU series airframe material composites comprising E-glass EW-185 and Carbon C522 Twill. The composite specimens were prepared to have the same size and thickness to minimize variability in the comparative analysis. The experimental study measures the transmission loss using S-parameters. At 5.3 GHz, the E-glass EW-185 fiber composite exhibits a material attenuation of -1.5 dB and a circular depolarization of 0.32 dB. The E-glass EW-185 fiber composite exhibits a material attenuation of -1.5 dB and a circular depolarization of 0.32 dB. In contrast, the Carbon C522 Twill fiber composite demonstrates a significantly higher material attenuation of -31.24 dB and a circular depolarization of 10.70 dB. Additionally, this paper examines the radiation pattern measurements of the CP-SAR antenna at various frequencies, providing a comprehensive analysis of the materials' impact on antenna performance.